PENGOLAHAN SAMPAH KERING DAN SAMPAH BASAH DI DESA GAMPANG KEC.PRAMBON KAB. SIDOARJO - Fanani, Achmad (Jurnal Abadimas Adi Buana, 2017)
KKN or social action internship for advanced university students is a program from PGRI Adi Buana Surabaya University. This program is really useful because society can get the education from the students and the students can get the education from society too. The student was divided into groups and they had to live in the village for 1 month. Before the student went to the village, they had been accepted some materials and training. The students would work with their program. One program that is about very important is waste recycled. Rubbish recycled is the program that must be applied in the Gampang village, one of the village that had chosen by PGRI Adi Buana Surabaya University. As we know that rubbish is divided into two, such as dry waste and wet waste. Dry waste is the waste that cannot be recycled by microbes such as plastic, bottles, cardboard, and etc. Wet waste is the waste that can be recycled by microbes. There were two ways to recycled the waste, the first one was to make a composter to recycled wet waste and the second one was to make plastic bag to recycled dry waste. The method that the student had used to imply the program was observation, questionnaires and counseling. The result that the students got was the product that made by the society such as composter and plastic bag.